Making high quality decisions in pregnancy: how should interventions which aim to improve decision quality be evaluated?. (18th April 2012) - Say, RE; Thomson, RG; Robson, SC
Abstract : Background: Increasing importance is placed on offering women choices about their obstetric care. Shared decision making (SDM) is an approach where patients and clinicians make decisions collaboratively combining the clinical expertise of health professionals with the personal expertise patients have of their preferences for options. Patient decision aids (PDAs) have been developed to facilitate SDM and improve the quality of decision making. This review aimed to identify and appraise the outcomes used in trials of PDAs for pregnant women to evaluate if they were fit for purpose. Methods: Randomised controlled trials evaluating PDAs for pregnant women were identified from electronic databases. The outcomes used were extracted and evaluated. Results: Twelve randomised controlled trials were identified. A wide range of different outcomes were used to evaluate PDAs for pregnant women. The most frequently used were knowledge (ten studies), anxiety (nine studies) and decisional conflict (eight studies). Two studies investigated maternal and perinatal outcomes finding that PDA use had no effect on them. The one study which evaluated length of consultation found PDA consultations were six minutes longer. Cost, adherence and litigation rates were not included as outcomes. Discussion: There is a lack of consensus in the literature on the most appropriate primary and secondary outcomes to use in trials of PDAs, limiting the opportunity for meta-analysis. It would be useful to agree standard outcomes for future trials and include measures which can assess whether PDA use increases the chance of a woman making a decision which matches her values and preferences.